Sexual attitudes and behavior patterns during and following pregnancy - Tolor, A; DiGrazia, P V (Archives of sexual behavior, 1976)
Changes in sexual attitudes and behavior patterns that might be associated with pregnancy and childbirth were investigated. The subjects were 216 women seen by a group of obstetricians and gynecologist in office practice. While there was a wide range of individual responses, in general a decline in sexual interest, activity, and satisfaction was reported as pregnancy progressed. The desire for body contact remained at a very high level throughout. Some changes in body zones regarded as most erogenous during the course of pregnancy were indicated. Following childbirth the women's sexuality seems to have returned to a normal level. The degree of liberal vs. conservative attitudes toward sex expressed by these women was not affected by the pregnancy, nor did this dimension relate significantly to other behavioral variables.